Dinamika Kewarganegaraan Liberal: Tantangan Global dan Masa Depan Hak Asasi Manusia - Ramadhan, Abhi Rachma; Nuriyani, Riska; Arpannudin, Iqbal; Putra, Muhammad Lathief Dwi; Adnin, Ismi (Ideas Publishing, 2024)
In the context of the era of globalization, liberal citizenship has become a major focus, influencing global politics and human rights. This research explores the role of the state, citizen participation, and the protection of individual rights, identifying obstacles to the implementation of the concept of liberal citizenship. Through content analysis methods and literature meta-analysis, this research explains the dynamics of liberal citizenship with a focus on Indonesia, revealing the complexity of the relationship between individual freedom and state responsibility. The research findings highlight political, cultural, and economic barriers to achieving ideal liberal citizenship. The implications show the need for careful regulations regarding technology adoption, improving law enforcement, and protecting human rights to create an inclusive and responsive society to global change.